(untitled) (Analysis in Theory and Applications, 2020)
The main aim of this study is to prove that a class of fractional Burgers' equations has a unique solution under some special conditions. Then it is demonstrated that an optimal control problem for this class of fractional Burgers' equations has at least one optimal solution.